Westonci.ca offers quick and accurate answers to your questions. Join our community and get the insights you need today. Discover precise answers to your questions from a wide range of experts on our user-friendly Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Sure, let's solve the given system of equations step-by-step using substitution:
[tex]\[ \begin{aligned} (1) & \quad x - 3y = 2 \\ (2) & \quad 2x + 5y = 15 \end{aligned} \][/tex]
### Step 1: Solve one of the equations for one variable
Let's solve equation (1) for [tex]\( x \)[/tex]:
[tex]\[ x - 3y = 2 \quad \Rightarrow \quad x = 2 + 3y \][/tex]
### Step 2: Substitute this expression into the other equation
Now we'll substitute [tex]\( x = 2 + 3y \)[/tex] into equation (2):
[tex]\[ 2(2 + 3y) + 5y = 15 \][/tex]
### Step 3: Simplify and solve for [tex]\( y \)[/tex]
First, distribute the 2 on the left side:
[tex]\[ 4 + 6y + 5y = 15 \][/tex]
Combine like terms:
[tex]\[ 4 + 11y = 15 \][/tex]
Subtract 4 from both sides to isolate the term with [tex]\( y \)[/tex]:
[tex]\[ 11y = 11 \][/tex]
Divide both sides by 11:
[tex]\[ y = 1 \][/tex]
### Step 4: Substitute [tex]\( y \)[/tex] back into the expression for [tex]\( x \)[/tex]
We have found [tex]\( y = 1 \)[/tex]. Substitute this value back into the expression [tex]\( x = 2 + 3y \)[/tex]:
[tex]\[ x = 2 + 3(1) \quad \Rightarrow \quad x = 2 + 3 \quad \Rightarrow \quad x = 5 \][/tex]
### Step 5: Write the solution
The solution to the system of equations is:
[tex]\[ \boxed{(x, y) = (5, 1)} \][/tex]
[tex]\[ \begin{aligned} (1) & \quad x - 3y = 2 \\ (2) & \quad 2x + 5y = 15 \end{aligned} \][/tex]
### Step 1: Solve one of the equations for one variable
Let's solve equation (1) for [tex]\( x \)[/tex]:
[tex]\[ x - 3y = 2 \quad \Rightarrow \quad x = 2 + 3y \][/tex]
### Step 2: Substitute this expression into the other equation
Now we'll substitute [tex]\( x = 2 + 3y \)[/tex] into equation (2):
[tex]\[ 2(2 + 3y) + 5y = 15 \][/tex]
### Step 3: Simplify and solve for [tex]\( y \)[/tex]
First, distribute the 2 on the left side:
[tex]\[ 4 + 6y + 5y = 15 \][/tex]
Combine like terms:
[tex]\[ 4 + 11y = 15 \][/tex]
Subtract 4 from both sides to isolate the term with [tex]\( y \)[/tex]:
[tex]\[ 11y = 11 \][/tex]
Divide both sides by 11:
[tex]\[ y = 1 \][/tex]
### Step 4: Substitute [tex]\( y \)[/tex] back into the expression for [tex]\( x \)[/tex]
We have found [tex]\( y = 1 \)[/tex]. Substitute this value back into the expression [tex]\( x = 2 + 3y \)[/tex]:
[tex]\[ x = 2 + 3(1) \quad \Rightarrow \quad x = 2 + 3 \quad \Rightarrow \quad x = 5 \][/tex]
### Step 5: Write the solution
The solution to the system of equations is:
[tex]\[ \boxed{(x, y) = (5, 1)} \][/tex]
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.